An investigation of Arabic speaking learners’ difficulties in the academic writing course - Elmahi, Abdallah (IJRDO- Journal of Educational Research, 2017)
Academic writing skills are of vital importance to the success and complete any academic majoratthe university level, yet the development of such skills is a challenge for many Arabicspeakingstudents, particularly those who graduated from schools where English is not thelanguage ofinstruction. It is essential to develop and evaluate strategies that can supportacademic writing skillsfor Arabic speaking students. This qualitative study evaluated a threecredit hours academic Englishcourse for academic writing intervention strategy designed tosupport Arabic speaking students atAbu Dhabi University. Data from the course showed twomajor areas of difficulty for participantsrelating to academic writing: difficulties constructingdifferent types of correct sentences inEnglish, and problems elaborating and supporting newparagraphs ideas in English. Theparticipants showed an improvement in terms of organizationand lay out of essays. Courses likethis intervention successfully meet the basic academic needsof Arabic speaking students, althoughongoing support is also needed.